2017
DOI: 10.1136/medethics-2015-103146
|View full text |Cite
|
Sign up to set email alerts
|

Should healthcare professionals sometimes allow harm? The case of self-injury

Abstract: This paper considers the ethical justification for the use of harm minimisation approaches with individuals who self-injure. While the general issues concerning harm minimisation have been widely debated, there has been only limited consideration of the ethical issues raised by allowing people to continue injuring themselves as part of an agreed therapeutic programme. I will argue that harm minimisation should be supported on the basis that it results in an overall reduction in harm when compared with more tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…); however, participants in this study reported a hypervigilance around self‐harm which often resulted in risk‐averse and controlling practices including seclusion and one‐to‐one observation. Current clinical management of self‐harm focuses largely on stopping the person engaging in acts of self‐harm (Sullivan ). The finding that mental health nurses’ approach to people who self‐harm is predominantly focused on prevention and control methods is therefore unsurprising and is in keeping with other studies (Dickinson et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…); however, participants in this study reported a hypervigilance around self‐harm which often resulted in risk‐averse and controlling practices including seclusion and one‐to‐one observation. Current clinical management of self‐harm focuses largely on stopping the person engaging in acts of self‐harm (Sullivan ). The finding that mental health nurses’ approach to people who self‐harm is predominantly focused on prevention and control methods is therefore unsurprising and is in keeping with other studies (Dickinson et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Pickard & Pearce ; Sullivan ). However, crucially within this approach is the need for the person to engage in psychological therapy to explore the function and meaning of their self‐harm to sustain longer term change and the development of alternative coping strategies (Edwards & Hewitt ; Sullivan ). Furthermore, a harm reduction approach also presents the opportunity to offer information and education to those who self‐harm which participants in this study reported doing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there has been a growing interest in harm‐minimization approaches for self‐injury, and such techniques have been advocated by some who suggest that a more baldly preventative approach can be distressing, stigmatizing and detrimental to the therapeutic relationship with professionals, and can contribute to behavioural escalation (Duperouzel & Fish, ; Holley, Horton, Cartmail, & Bradley, ; Lindgren, Öster, Åström, & Graneheim, ; Pembroke, ; Shaw, ). Much debate around the use of harm‐minimization approaches has been rooted in non‐empirical discussions of ethics and legalities, much of whose tone suggests a stark binary choice between adopting or proscribing such techniques (e.g., Edwards & Hewitt, ; Gutridge, ; Sullivan, ). In the UK, official guidance is to recommend “tentative approaches to harm reduction for some people who self‐harm in the community ” (National Institute for Health and Clinical Excellence, , p. 259.…”
Section: Introductionmentioning
confidence: 99%
“…I would like to thank Hannah Pickard and Stephen Pearce for their informed and clinically focused response to my paper on harm minimisation 1. They argue that harm minimisation is not a viable or responsible approach within an inpatient environment 2…”
mentioning
confidence: 99%